Prevalence of Bacillus cereus in food and hand swabs of night market food vendors and its relationship with their food safety knowledge, attitude, and practices - Abdul Rahim, Noor Aniza; Ungku Zainal Abidin, Ungku Fatimah; Radu, Son; Selamat, Jinap; Abdul Mutalib, Noor Azira (Rynnye Lyan Resources, 2024)
This paper aimed to determine Bacillus cereus prevalence in food and hand swab samples and its relationship with the level of knowledge, attitude, and practices (KAP) of the food vendors in the night market in northern Perak, Malaysia. A total of 140 cooked food and hand swab samples were collected in this study. About 28% (N = 83) of food and 42% (N = 57) of the food handlers’ hands were detected with B. cereus. The KAP results of the food handlers showed a (mean ± SD) moderate knowledge score (73.96±15.79%), good attitude score (91.61±7.48%), and high practices score (81.70±11.94%). Further analysis revealed that the attitude of vendors independently influenced their practices. In addition, knowledge and practice scores were found to be significantly related to B. cereus hand carriage. Hence, the findings from this study act as an eye-opener for the authorities to improve awareness of food safety and stress the importance of good attitude and hygiene practices, especially among small food vendors.